DTS-100G — a versatile heterogeneous MPSoC board for cryogenic sensor readout. (28th February 2023) - Muscheid, T.; Boebel, A.; Karcher, N.; Vanat, T.; Ardila-Perez, L.; Cheviakov, I.; Schleicher, M.; Zimmer, M.; Balzer, M.; Sander, O.
Abstract: Heterogeneous devices such as the Multi-Processor System-on-Chip (MPSoC) from Xilinx are extremely valuable in custom instrumentation systems. This contribution presents the joint development of a heterogeneous MPSoC board called DTS-100G by DESY and KIT. The board is built around a Xilinx Zynq Ultrascale+ chip offering all available high-speed transceivers using QSFP28, 28 Gbps FireFly, FMC, and FMC+ interfaces. The board is not designed for a particular application, but can be used as a generic DAQ platform for a variety of physics experiments. The DTS-100G board was successfully developed, built and commissioned. ECHo-100k is the first experiment which will employ the board. This contribution shows the system architecture and explains how the DTS-100G board is a crucial component in the DAQ chain.